2022
DOI: 10.1155/2022/3481423
|View full text |Cite
|
Sign up to set email alerts
|

Regional Alteration within the Cerebellum and the Reorganization of the Cerebrocerebellar System following Poststroke Aphasia

Abstract: Recently, an increasing number of studies have highlighted the role of the cerebellum in language processing. However, the role of neural reorganization within the cerebellum as well as within the cerebrocerebellar system caused by poststroke aphasia remains unknown. To solve this problem, in the present study, we investigated regional alterations of the cerebellum as well as the functional reorganization of the cerebrocerebellar circuit by combining structural and resting-state functional magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…(Schmahmann and Caplan, 2006;Reetz et al, 2012), such as the regulation of language and working memory (Nitschke et al, 2005;Schmahmann et al, 2019). Previous studies have revealed the functional alternations of the CPL in stroke (Li et al, 2013;Tang et al, 2016;Fan et al, 2019;Zhang et al, 2022). For example, Li et al (2013) found, relative to HCs, stroke participants showed reduced FCs between the bilateral cerebellar lobule IX and the ipsilesional prefrontal cortex (medial part of the prefrontal cortex and dorsolateral prefrontal cortex) and lateral parietal cortex.…”
Section: Functional Connectivity Alterations In the Cerebellum Poster...mentioning
confidence: 95%
See 2 more Smart Citations
“…(Schmahmann and Caplan, 2006;Reetz et al, 2012), such as the regulation of language and working memory (Nitschke et al, 2005;Schmahmann et al, 2019). Previous studies have revealed the functional alternations of the CPL in stroke (Li et al, 2013;Tang et al, 2016;Fan et al, 2019;Zhang et al, 2022). For example, Li et al (2013) found, relative to HCs, stroke participants showed reduced FCs between the bilateral cerebellar lobule IX and the ipsilesional prefrontal cortex (medial part of the prefrontal cortex and dorsolateral prefrontal cortex) and lateral parietal cortex.…”
Section: Functional Connectivity Alterations In the Cerebellum Poster...mentioning
confidence: 95%
“…For CAL, stroke participants showed increased FCs between the ipsilesional anterior inferior cerebellum and superior cerebellum (Wang et al, 2010) and between the right anterior inferior cerebellum and left middle frontal gyrus (MFG) (Yin et al, 2014) compared with healthy controls (HCs). While, for CPL, stroke participants showed increased FCs between the ipsilesional CPL and the contralesional primary motor cortex (Yin et al, 2012), and reduced FCs between the bilateral cerebellar lobule IX and the ipsilesional medial part of the prefrontal cortex, dorsolateral prefrontal cortex, lateral parietal cortex (Li et al, 2013), between the right CPL and left precentral gyrus (PreCG), inferior frontal gyrus (IFG), inferior parietal lobule (IPL), middle temporal gyrus (MTG) (Tang et al, 2016), between the bilateral CPL and left IPL (Fan et al, 2019), and between the right cerebellar lobule VI and left PreCG (Zhang et al, 2022) compared with HCs. These findings demonstrated that the spontaneous brain activities in the cerebellar subregions were disrupted by stroke, and the CAL and CPL experienced different functional reorganization patterns after stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The historical process of Han migration to southern China led to the assimilation of Zhuang people and had a negative impact on Zhuang people identity. Zhuang people's way of life, language habits and other aspects are deeply influenced by the integration of Chinese culture, the boundary of national identity is more vague, the "Zhuang" became the imagined community of many young people who were only related to the Zhuang and were deeply influenced by Han culture (Zhang et al, 2022). Zhuang people has become almost entirely sinicized after a long period of integration, with the majority belonging to the sinicized Zhuang people, despite the preponderance of the ethnic minority population.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies of Alzheimer’s disease, Parkinson’s disease and aphasia have confirmed that the cerebellum may be involved in modifying the performance of learned sequences such as cycling that are based on procedural memory-related brain activity (cerebellum–striatum–frontal circuit) [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%